Dormancy induction by summer temperatures and/or desiccation in imbibed seeds of trumpet daffodils Narcissus alcaracensis and N. longispathus (Amaryllidaceae). (9th May 2016) - Herranz, J. M.; Copete, E.; Copete, M. A.; Márquez, J.; Ferrandis, P.
Abstract: We analysed the effects of summer temperatures (28/14 °C) and/or desiccation (from 48% to 8% humidity) on imbibed Narcissus alcaracensis and N. longispathus seeds with an elongating embryo. In the N. alcaracensis seeds that overcame dormancy (embryo elongation = 27.14%), exposure to high temperatures induced secondary dormancy and reduced subsequent embryo growth. A further 3‐month cold stratification (5 °C) was required to break secondary dormancy. Desiccation in early embryo growth stages (elongation = 11.42%) also reduced germination. Desiccation in the seeds in a more advanced growth stage ( i.e . embryo elongation = 27.14%) induced secondary dormancy, which the further 3‐month cold stratification did not overcome. When desiccation was preceded by high temperatures, seeds better overcame secondary dormancy ( i.e . longer embryo elongation and seed germination). Treatments did not affect seed viability. In the N. longispathus seeds that overcame dormancy (embryo elongation = 59.21%), exposure to high temperatures induced secondary dormancy and they needed a further 1‐month stratification at 15/4 °C + 2 months at 5 °C to reactivate the germination process. When embryo elongation was 42.10%, seed desiccation totally impeded subsequent germination. When embryo elongation reached 59.21%, desiccation induced secondary dormancy, which was not overcome by the above‐described stratification treatment. When desiccation was preceded by high temperatures, seeds better overcame dormancy. Stress treatments killed 5–10% of seeds. This study suggests that the seeds of species with complex morphophysiological dormancy (MPD) levels are sensitive to desiccation in early embryo development stages, as opposed to the seeds of species with deep simple epicotyl MPD, which better tolerate water stress.